PENGARUH UMUR BETON PADA PENGUJIAN INTEGRITAS FONDASI TIANG BOR - suantoro wicaksono (Direktorat Bina Teknik Jalan dan Jembatan, 2022)
Integrity testing on deep foundations,better known as its trademark PIT, is one of the tests that aims to determine the integrity of the foundation. Integrity can be in the form of the length of the pile and the enlargement and/or downsizing of the pile foundation. There is no standard that regulates the minimum age of concrete when the integrity test is carried out, but it is often carried out after the age of 28 days of concrete with a wave propagation value of Ws=3,800 m/s and there is no correction value if the test is carried out at a concrete age fewer than 28 days. The research was conducted to test the integrity using PIT on the bored pile in the Bromo area, where the age of the concrete when tested was 1 and 11 days. Based on the results of the study, it was found that there was a difference in the displacement of the concrete enlargement of 11.5% on the tested bored pile. However, with reference to that the PIT integrity test is a quality test, not quantity test, so that the effect of concrete age on integrity testing, especially using PIT, can be ignored. Key words: integrity test, deep foundation, bored pile, concrate age, deep foundation, wave speed.